Injuries in women's football: A systematic review of the research - Stanković Mima (College of Sports and Health, Belgrade, 2019)
Women's football is striving to become the most popular women's team sport, as is the case with men's football. Women's football in the Republic of Serbia is practically in its initial stages, although lately there has been a greater interest among young girls for this sport. The most frequent injuries in women's football, as well as in men's, are injuries to the lower extremities (65%), the most frequent of which are knee and ankle injuries (Junge, & Dvorak, 2007). In this overview 14 papers were analysed, written between 2000 and 2018. According to the current research, we could conclude that injuries in women's football most frequently appear in the region of the lower extremities, especially to the knees and ankles. In case of the knee injury, it usually comes in the form of a rupture of the anterior cruciate ligament. Most injuries occur during training, and are non-contact injuries. When it comes to the timeline, injuries are most frequent at the beginning and the end of the season. At the beginning, injuries occur since players are inactive in the transition period, and at the end due to inadequate planning and programming of the training process and insufficient shape. Players who are technically better trained and have greater possession of the ball during the game are more susceptible to injuries than other players. It is very important that the training process is carried out adequately and professionally by the coaches and sports professionals. Programs designed for the prevention of injuries decrease the number of injuries, but cannot fully prevent the possibility of an injury.